Can you see me? - Scott, Libby; Westcott, Rebecca (Scholastic Press, 2020)
Eleven-year-old Tally is starting sixth grade at Kingswood Academy and she really wants to fit in, which means somehow hiding her autism, hypersensitivity to touch, and true self, and trying to act "normal" like her former best friend, Layla, who is distancing herself from Tally and her fourteen-year-old sister, Nell, who is always angry with Tally for being different; but as she records her thoughts and anxieties in her coping diary, Tally begins to wonder--what is "normal" anyway?